Socio-demographic correlates of total and domain-specific sedentary behavior in Latin America : a population-based study - Moraes Ferrari, Gerson Luis de (2020)
Fil: Moraes Ferrari, Gerson Luis de. Universidad de Santiago de Chile. Facultad de Ciencias Médicas. Laboratorio de Ciencias de la Actividad Física, el Deporte y la Salud; Chile